Fragmentation assessment in caving mining: operational evidence from Chuquicamata underground mine - Divasto Vergara, C.; Barindelli Pizarro, G.; Quiroz Alegría, R. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
A quantitative fragmentation assessment is presented for the Chuquicamata underground mine based on the integration of operational evidence obtained from drawpoint granulometric mapping, records of secondary breakage of oversized fragments, and production extraction reports. The study focuses on the macroblocks MB N01-S01, MB N02-N03, and MB S02-S03, using a comprehensive multi-source database collected between 2019 and 2025. This database comprises more than 7,500 drawpoint inspections, 5,000 geometric measurements of rock fragments, and a continuous record of secondary breakage events. This robust dataset enables a comprehensive evaluation of fragmentation behaviour at the drawpoint scale under deep caving mining conditions. The analysis examines the relationship between observed fragmentation, the basic geotechnical units (BGUs) model and the extraction height, with the primary objective of identifying systematic trends in granulometric evolution as caving progresses. Furthermore, operationally derived fragmentation results are compared with the prognosis developed by SRK in 2021 for the first lift of extraction (Lift 1). The findings indicate that the measured fragmentation is consistently finer than projected across the analysed sectors, revealing critical deviations in specific units such as the Potassic East Porphyry unit, where models based on discrete fracture network and block caving fragmentation (DFN-BCF) methodology significantly overestimated the rock mass competency and blockiness. Moreover, the results suggest that the model algorithm underestimates the fines fraction due to the comminution process inherent to secondary fragmentation. Fundamental contributions of this research include identifying a tendency towards more elongated geometries as fragment size increases, which contradicts the traditional spherical assumption commonly used in theoretical estimations. Additionally, the study demonstrates that recorded secondary breakage events constitute a more robust and statistically representative operational proxy for tracking the oversize fraction than visual drawpoint mapping, which is biased toward the fines fraction. Nevertheless, both the frequency of secondary breakage and P80 values from field mapping reflect a consistent tendency to progressively decrease as extraction height increases.